Optimization and Efficiency of Spot Welding Process: Waste Reduction Through the Value Stream Mapping Approaches - Amallia Amallia; Dhea Intan Patya; Rizki Aulia Nanda; Agus Supriyanto (Lembaga Pengembangan Kinerja Dosen, 2026)
A four-wheeled vehicle bracket component manufacturing company experienced a surge in demand for a hook transport product. However, the production process was found to be inefficient due to the presence of non-value-added activities and barriers. The objective of the research was to identify and minimize waste in the production of spot welding, as well as to determine the takt time for hook transport production. To this end, a Value Stream Mapping (VSM) analysis was conducted, leveraging the existing VSM framework to assess the production process's efficiency for identify and eliminate non-value-added activities. The analysis revealed that the cycle process efficiency prior to the implementation of improvements stood at 74%, characterized by various forms of waste, including defects, over-processing, waiting, and motion. The subsequent improvement, as depicted in the anticipated future state value stream mapping, resulted in a 94% enhancement in cycle process efficiency, representing a 20% increase. Beyond the efficiency cycle process outcome, the takt time calculation for spot welding production set yielded a value of 52.85 seconds per product. This indicates that the takt time required for hook transport cycle production to meet consumer demand is 52.85 seconds. The implementation of the VSM method is expected to facilitate the identification and reduction of production waste, enhance efficiency, and optimize the fulfillment of demand targets.